A Designed Ladder‐Type Heteroarene Benzodi(Thienopyran) for High‐Performance Fullerene‐Free Organic Solar Cells. Issue 12 (20th November 2017) - Wu, Hao; Fan, Haijun; Xu, Shengjie; Zhang, Cheng; Chen, Shanshan; Yang, Changduk; Chen, Daoliang; Liu, Feng; Zhu, Xiaozhang
Abstract : To meet the imminent requirement of fullerene‐free electron acceptors, a new ladder‐type heteroarene benzodi(thienopyran) (BDTP) is designed and synthesized by embedding pyran rings in [2, 2‐(2, 5‐dialkyloxy‐1, 4‐phenylene)dithiophene] (PDT) for organic photovoltaic (OPV) applications. Originating from the strong p–π conjugation of the oxygen atom in the pyran rings, electron‐rich BDTP results in the BDTP‐cored molecular acceptor, NBDTP, with strong intramolecular charge transfer effect. With sp 3 carbons in pyran rings, NBDTP have the flexibility of targeted modification to resolve the solubility as well as the morphological tuning by handy alkyl chain attachment. As a result, the fusion of pyran rings in BDTP means that the acceptor exhibits a narrow optical band gap of 1.58 eV and a high LUMO energy level of −3.79 eV. Meanwhile, blend morphology of NBDTP‐based OPVs shows fine tunability via thermal annealing. Owing to the beneficial optical absorption, suitable energy‐level alignment, favorable molecule packing, and proper morphology, the optimized NBDTP‐based OPVs achieve a power conversion efficiency of up to 10.1%, which exemplifies the potential of utilizing molecular acceptors featuring ladder‐type heteroarenes for high‐performance OPVs. Abstract : By embedding pyran rings in PDT, a novel ladder‐type heteroarene, BDTP, is constructed to design a high‐performance non‐fullerene acceptor NBDTP for organic photovoltaic applications. The fused pyran rings endows NBDTP with favorable energy‐level alignment and proper blend morphology, delivering a power conversion efficiency of over 10%, suggesting the BDTP core is a very promising building block for organic optoelectronic applications.